Reply to "successful early use of anti-SARS-CoV-2 monoclonal neutralizing antibodies in SARS-CoV-2 infected hematological patients-A Czech multicenter experience": A case series of SARS-CoV-2 Omicron infection and aggressive lymphoma in the Sotrovimab era - Cassin, Ramona; Rampi, Nicolo; Anna Fidanza, Cecilia; Muscatello, Antonio; Mariani, Bianca; Noto, Alessandro; Rossi, Francesca Gaia; Baldini, Luca (Hematological oncology, 2023)
A prospective multicentre experience of early administration of anti-SARS-CoV-2 spike protein neutralizing monoclonal antibodies (MA) with efficacy among patients with hematological malignancies and early-stage COVID- 19 was reported by Weinbergerová et al. The study validated the safety and efficacy of MA early use among hematological patients with newly diagnosed early-stage COVID-19 in terms of alleviating infection course and decreasing mortality. However no reference to new variant (Delta and Omicron) or other MA (e.g., Sotrovimab) has been reported. We reported our monocentric experience of 8 aggressive lymphoma patients with Omicron infection, 7 of whom treated with this MA in our Institution between December 2021 and February 2022. Among the patients treated with Sotrovimab nobody experienced neither SARS-CoV2 reactivation, nor other infectious events. One patients on active lymphoma treatment was hospitalized for pneumonia and treated with remdesivir. In 4/8 patients negativization of molecular swab occurred concomitantly to symptoms resolution with a median of 5.25 days, while the other 4 patients remained persistently positive with a median of 26.3 days. In this group, in order to maintain the chemo/chemoimmunotherapy (CT/CIT) dose-density, lymphoma treatment was reassumed independently on molecular swab analysis. SARS-CoV-2 negativization occurred with a median of 7.7 days after the resumption of CT/CIT. The one patient treated with remdesivir, although still positive to molecular swab, restarted R-COMP regimen at symptoms resolution too, but experienced an Omicron pneumonia exacerbation. This is the first case series reported in literature of patients affected by Omicron variant in which Sotrovimab seems to provide a resolution of COVID-19 disease, even in patient with molecular swab positive persistence too. Patients with aggressive lymphoma histologies should not be deprived of the best available treatment of their disease after sotrovimab administration, even in the presence of a still positive Omicron swab.
Keywords: lymfom; monoklonální protilátky; RNA, Viral; RNA virová; Antibodies, Monoclonal; aggressive lymphoma; COVID-19; Humans; Česká republika; SARS-CoV-2; prospektivní studie; lidé; Lymphoma; omicron; monoclonal antibody; Czech Republic; Prospective Studies